Clostridium difficile Infection. (April 2017) - Phillips, Jennan A.; Hammond, Stephanie
Preventing Clostridium difficile, the most common cause of health care–associated infections in hospitals and infectious disease death in the United States, is a national priority. Increased rates of infection among low-risk individuals in the community call for community-based prevention efforts to halt the increasing spread of this highly contagious opportunistic infection.